If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-z/12=5
We simplify the equation to the form, which is simple to understand
-z/12=5
We move all terms containing z to the left and all other terms to the right.
-0.083333333333333z=+5
We simplify left and right side of the equation.
-0.083333333333333z=+5
We divide both sides of the equation by -0.083333333333333 to get z.
z=-60
| 4w^2-5=9w | | 4m+5(m+2)=1 | | 8x-(4x+8)=8 | | dx+g=0 | | 3x+-2y=zfory | | 3r=-45 | | -0.6+0.5x+4=5 | | 5(x+2)+4x=55 | | 2m-9m=12 | | 3m^2-18=0 | | 25(b+826)-804=-29 | | P=120-0.03x | | 3r+11s= | | 5N(-8+4T)= | | 3(w-93)+99=24 | | Y=lnex^2-1 | | 0.16(y-7)+0.18y=0.14y-0.05(10) | | 6x-4+4x+17-9x=34 | | 6w+z-5w-z= | | 3(n-4)=3 | | 15+(2+x)=(15+2)+x | | 14.5=3.4(z-12.8)-2.5 | | 3+4(2x-3)-5x=16+5 | | 10p^2-8p-14=0 | | Cos(x)=y | | 4z-10-9z= | | -4/7y=32 | | -2.36(g+3)=0 | | 2x-4-6x+1= | | -9c-2=-(-5c+2)+4(3-5c) | | 2.8-z=1.08 | | (3u-27)(u^2+6u-7)=0 |